The emerging roles of METTL1-mediated tRNA m7G methylation in cancer development and immunotherapy - Wang, Qiang; Jiang, Xiulin; Yuan, Yixiao; Li, Chunhong (Frontiers in Immunology, 2026)
RNA modifications, particularly N7-methylguanosine (m7G), have emerged as critical epigenetic regulators in cancer biology. METTL1, a conserved S-adenosylmethionine-dependent methyltransferase, catalyzes m7G modification primarily on tRNA, often in complex with its cofactor WDR4. This modification stabilizes tRNA structure, protects it from degradation, and enhances the translation efficiency of specific codons, thereby enabling selective protein synthesis. Aberrant METTL1 expression has been observed across multiple cancer types—including lung, liver, colorectal, gastric, breast, cholangiocarcinoma, esophageal, glioma, head and neck, and thyroid cancers-where it promotes tumor proliferation, metastasis, therapy resistance, and metabolic reprogramming. Mechanistically, METTL1-mediated tRNA m7G modification influences downstream mRNA stability and translation, affecting oncogenes, drug resistance genes, and key metabolic regulators. Moreover, METTL1 shapes the tumor immune microenvironment by modulating immune cell infiltration, promoting immunosuppressive populations, and contributing to immune evasion, which has implications for immunotherapy. Collectively, METTL1 functions as a pivotal driver of cancer progression and represents a promising biomarker and therapeutic target, highlighting the potential of targeting tRNA m7G modification in precision oncology.